Synthesis of water-soluble hypervalent iodine reagents for fluoroalkylation of biological thiols - Klimánková, Iveta; Hubálek, Martin; Matoušek, Václav; Beier, Petr (Organic & biomolecular chemistry, 2019)
New open-chain and water-soluble hypervalent iodine reagents were synthesized and used for the transfer of fluoroalkyl groups to sulfur atoms of cysteine and cysteine-containing peptides under biocompatible conditions. Some of the reagents displayed excellent reactivity despite their limited stability in aqueous media. In reactions with a short cysteine-containing peptide, in addition to the expected S-fluoroalkylated product, a range of side-products were obtained. The amount of side-products depended on the conditions used (type of reagent, concentration, and pH). With highly activated hypervalent iodine reagents, a new reactive mode was observed - reaction with disulfides to form fluoroalkyl thiols.
Keywords: alkylace; molekulární struktura; Indicators and Reagents; Iodine; jod; voda; Solubility; Hydrocarbons, Fluorinated; Water; Molecular Structure; rozpustnost; Sulfhydryl Compounds; fluorované uhlovodíky; Alkylation; sulfhydrylové sloučeniny; indikátory a reagencie